2016
DOI: 10.4238/gmr.15017389
|View full text |Cite
|
Sign up to set email alerts
|

Association of IL-18 polymorphisms with rheumatoid arthritis: a meta-analysis

Abstract: ABSTRACT. , an important proinflammatory cytokine, has been reported to play a potential pathological role in rheumatoid arthritis (RA). Results from previous studies on the association between IL-18 polymorphisms and RA are conflicting. To clarify this, an updated meta-analysis of all available studies on IL-18 polymorphisms and RA was conducted. Eligible articles were identified by searching databases, including PubMed, Ovid, Cochrane Library, EMBASE, and China Knowledge Resource Integrated Database, for the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…These polymorphisms may be associated with increased IL16 and IL18 synthesis in some patients and enhanced inflammatory response. Previous studies have shown that these polymorphisms may be associated with increased risk of inflammatory diseases [14]. The aim of this study was to examine the association between IL16 and IL18 gene polymorphisms and GDM.…”
Section: Introductionmentioning
confidence: 99%
“…These polymorphisms may be associated with increased IL16 and IL18 synthesis in some patients and enhanced inflammatory response. Previous studies have shown that these polymorphisms may be associated with increased risk of inflammatory diseases [14]. The aim of this study was to examine the association between IL16 and IL18 gene polymorphisms and GDM.…”
Section: Introductionmentioning
confidence: 99%
“…In RA, articular inflammation seems to be caused by the expression of inflammatory cytokines and chemokines that determine the activation and proliferation of the synovial lining, and by inflammatory cell recruitment and B cell activation with autoantibody production (Samson et al, 2012). The IL-1 family of cytokines (IL-1a, IL-1b, IL-18, and IL-33) are highly expressed in RA (Bessis et al, 2000;Li et al, 2016). Furthermore, IFN-b, TGFb, IL-4, and IL-13 increase the expression of IL-1Ra while diminishing the production of IL-1 (Chizzolini et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Also, monocytes and macrophages in patients with rheumatic diseases, especially SLE, have increased expression of inflammasome components and/or enhanced inflammasome activation , suggesting the existence of an intrinsic alteration in the intracellular inflammasome pathways. Of note, some polymorphisms of inflammasome‐related genes have been shown to be associated with susceptibility, severity, and/or treatment response in rheumatic diseases, including SLE and RA . Improvement in disease activity was observed in murine models of SLE, RA, crystal‐induced arthropathies, and SjĂśgren's syndrome (SS) when inflammasome activation was targeted genetically or chemically (see details below).…”
Section: Introductionmentioning
confidence: 99%
“…Cytokine polymorphisms have not been definitive either. Polymorphisms of IL‐1β may be associated with the development of RA in certain ethnic populations , and IL‐18 polymorphisms may also increase the risk of RA . Overall, the relationship between RA and the inflammasome may reflect the inflammatory activity in the joint itself, rather than a true genetic etiology of the disease.…”
Section: Introductionmentioning
confidence: 99%